The effects of foreign product demand-labor transfer nexus on human capital investment in China - Hui Hu; Yuqi Zhu; Chien-Chiang Lee; Alastair M. Morrison (Humanities & Social Sciences Communications, 2023)
Abstract Using about 73,000 individuals’ data in China, this research, for the first time, analyzes the impact of labor transfer (LT) caused by foreign product demand (FPD) on human capital investment. Two-stage least squares estimation with the instrumental variable is applied and produced three findings. First, the FPD-LT model illustrates that with FPD increasing, more labor transfers from the agricultural sector to the non-agricultural sector. Second, working in the non-agricultural sector requires higher-level skills than in the agricultural sector. LT from agricultural sector to non-agricultural sector motivates people to invest more in human capital and promotes gender equality in human capital investment. Third, labor transferring from the agricultural sector to the non-agricultural sector enhances individuals’ income, leading to the increase of children’s human capital investments. The better-educated people make greater investment in their children’s human capital, exacerbating intergenerational inequality.